Mortality due to cardiovascular disease in women during the reproductive age (15 to 49 years), in the State of São Paulo, Brazil, from 1991 to 1995 - Haddad,Nagib (2000)
OBJECTIVE: To describe mortality due to cardiovascular diseases in women during the reproductive age (15 to 49 years) in the state of São Paulo, Brazil, from 1991 to 1995. METHODS: A list of all deaths and their underlying causes, coded according to the International Classification of Diseases, 9th revision, multiple causes of death, and estimates of the female population according to age groups were provided by the SEADE Foundation. Specific coefficients for 100 thousand women for each year as well as the medians of these coefficients related to 5 years, and the percentage of death by subgroups were calculated. RESULTS: Cerebrovascular diseases have the highest coefficients (14.24 for 100 thousand females), followed by ischemic heart disease (7.37), other heart diseases (6.39), hypertensive disease (3.03), chronic rheumatic heart disease (1.58), pulmonary vascular diseases (1.29), and active rheumatic fever (0.05). Systemic arterial hypertension, as an associated cause, occurred in 55.3% to 57.8% of all the deaths due to intracerebral hemorrhage and in 30.4% to 30.8% due to subarachnoid hemorrhage. CONCLUSION: The significance of cerebrovascular diseases, coronary artery disease, and systemic arterial hypertension as causes of mortality suggests the need to emphasize preventive actions for young women who have the potential to reproduce to avoid possible complications in future pregnancies, and premature mortality.